WRITING DAILY STATUS ON SOCIAL MEDIA: CODE-MIXING AND CODE-SWITCHING PHENOMENA: A LITERATURE REVIEW - Mewengkang, Carolina; Fansury, Andi Hamzah (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study aimed to analyze the use of code-mixing and code-switching, specifically found in social media, such as Instagram Tik Tok and Facebook daily status. The design of this research review is a descriptive qualitative study since it focused on the phenomenon of code-mixing and code-switching. Related to that, in this study, the researcher focused on articles code-mixing and code-switching use. Moreover, the data were collected by examining several articles. The study result shows that the reasons for using code-mixing and code-switching are discussed in a particular topic, where all of the selected subjects picked that reason. However, the researcher found three additional reasons out that: Some of the influencers have different reasons why use code-mixing or code-switching, such as changing topic, lack of vocabulary, practice, English mastery, bilingual/multilingual, and trend.